Management of human capital in higher education: analysis of a university - Cuentas Martel, Susan Carol (2018)
The present society, characterized by the unceasing development of science and knowledge, demands from the universities a renewal of management, where the people who produce knowledge are the center, that is, a human capital management. In this sense, this article presents an investigation that analyzes the Strategies of Human Capital Management with respect to the teachers in the Faculty of Education of a university of Lima. The methodology is mixed, quantitative and qualitative. Interviews and surveys were applied to managers and teachers, respectively, and information was obtained on strategies aimed at valuing and promoting human capital in the institution, although the results showed that these are insufficient, emphasizing the institutional commitment of teachers.